Efficacy of cold atmospheric plasma for inactivation of viruses on raspberries - Velebit Branko; Milojevic Lazar; Baltic Tatjana; Grkovic Nevena; Gummala Sanjay; Velebit Marina; Skoko Ines; Mojsova Sandra; Putnik Predrag (Elsevier, 2022)
In this study, the effectiveness of cold atmospheric plasma (CAP) in inactivating murine norovirus (MNV/human norovirus surrogate) and hepatitis A virus (HAV) on aerosol-inoculated dark red Willamette raspberries was explored. Pulsed positive corona discharge system fed by synthetic air was used for the production of CAP. Raspberries were treated for 1, 3, 5, 7, and 10 min at 25 W. Application of CAP enabled a 4 log10 infectivity reduction in <5 min for MNV and approximately 10 min for HAV (from starting level of 6.91 and 7.84 log10 PFU/mL, respectively). Viral genome copies reduction of 3.18 log10 for MNV and 4.32 for HAV were found from starting level of 5.76 and 6.47 log10 gc/μL, respectively. CAP treatment did not result in significant degradation of fruit color, an important quality attribute. The study demonstrated CAP as an efficient post-harvest decontamination method to reduce viral load in raspberries without significantly affecting its quality parameters. Industrial relevance Due to the fast-processing paces required in the raspberry industry, it is difficult to assure the complete microbiological safety of this fruit. Cold atmospheric plasma is a practical, environmentally-friendly, non-thermal tool for the effective reduction of microbial pathogens. The model developed in this study demonstrated that CAP treatment of fresh raspberries not only inactivated hazardous enteric viruses in a short time (10 min) but also unaffected fruit color stability. The simplicity of described CAP design and low-cost inputs (air and electricity) enable the commercial application of inexpensive plasma chambers for continuous surface decontamination of large volumes of raspberries without bringing processing to a standstill.
Keywords: Norovirus; Hepatitis A virus; Cold plasma; Inactivation; Raspberries